Comment on "Cut-off points to identify sarcopenia according to European Working Group on Sarcopenia in Older People (EWGSOP) definition". Issue 6 (December 2016) - Coraci, Daniele; Santilli, Valter; Padua, Luca
Summary: Bahat and colleagues presented cut-off values for muscle mass and strength and calf circumference for correct application, in Turkish population, of European Working Group on Sarcopenia in Older People criteria. The work is important to assess this condition on the basis of population-specific data. Ageing care represents a target of modern medicine and sarcopenia, consequence of it, can worse the quality of life. Assessing this, considering population characteristics, as authors described, is very functional in medical practice. We would suggest consideration of people older than 90 years as different elderly subclass and application of technological tools to monitor muscular performance.